PF.10 The PLUTO Study: Evaluation of the Effectiveness of Percutaneous Vesicoamniotic Shunting (VAS) For Lower Urinary Tract Obstruction (LUTO), a Comparison of RCT and Registry Data. (26th April 2013) - Morris, RK; Malin, GL; Quinlan-Jones, E; Middleton, LM; Khan, KS; Deeks, JJ; Kilby, DM
Abstract : Objective: RCT and registry to determine effectiveness of VAS in LUTO for survival and renal function. Setting: Fetal Medicine departments (England, Scotland, Ireland, Netherlands). Participants: Pregnant women with singleton, male fetus with isolated LUTO. Design: RCT with registry. Intervention - VAS compared to conservative care. Main Outcome Measures: Perinatal mortality and serum creatinine at 6 weeks of age and 1 year. Prognostic value of gestational age and liquor volume at diagnosis were assessed in a logistic regression analysis using data from registry and RCT. Results: RCT survival to 28 days favoured VAS: intention-to-treat relative risk 1.88, 95%CI: 0.71 to 4.96 (50% v 27%, p = 0.27); registry favoured conservative management: relative risk 0.58, 95%CI: 0.26, 1.29 (40% v 69%, p = 0.14). Those women who entered the registry and had conservative management were more likely to have a normal liquor volume at diagnosis (>5th centile) than those receiving VAS (p = 0.04) or those randomised (p = 0.03). They also had a higher proportion with gestational age at diagnosis >24 weeks compared with those randomised (p = 0.002). These variables were strongly associated with improved survival to 28 days in a multivariate logistic regression analysis. There was also a difference in the pathological diagnoses made postnatally in the conservative group in the registry with a 5/21 (24%) of babies with a false positive antenatal diagnosis of LUTO. Conclusion: Normal liquor volume (>5th centile) and age at diagnosis > 24 weeks seem to be associated with increased probability of survival at 28 days in fetuses with confirmed LUTO.